New Self-Adaptive Algorithms and Inertial Self-Adaptive Algorithms for the Split Variational Inclusion Problems in Hilbert Space. (4th July 2022) - Chuang, Chih-Sheng; Hong, Chung-Chien
Abstract: In the field of convex optimization, numerous problems can be modeled as the split variational inclusion problem. In this paper, we want to give self-adaptive algorithms and inertial self-adaptive algorithms to study the split variational inclusion problems. Next, we propose related convergence theorems under suitable conditions.